Urinary tract infections in children: an overview of diagnosis and management - Meredith Temple-Smith; Jonathan Kaufman; Lena Sanci (BMJ Paediatrics Open)
Urinary tract infections (UTIs) are a common and potentially serious bacterial infection of childhood. History and examination findings can be non-specific, so a urine sample is required to diagnose UTI. Sample collection in young precontinent children can be challenging. Bedside dipstick tests are useful for screening, but urine culture is required for diagnostic confirmation. Antibiotic therapy must be guided by local guidelines due to increasing antibiotic resistance. Duration of therapy and indications for imaging remain controversial topics and guidelines lack consensus. This article presents an overview of paediatric UTI diagnosis and management, with highlights of recent advances and evidence updates.